Low Temperature Growth of Single-walled Carbon Nanotube Forest - Lee, Il-Ha; Im, Ji-Woon; Kim, Un-Jeong; Bae, Eun-Ju; Kim, Kyoung-Kook; Lee, Eun-Hong; Lee, Young-Hee; Hong, Seung-Hun; Min, Yo-Sep (Bulletin of the Korean Chemical Society, 2010)
Forest of single-walled carbon nanotubes (SWNTs) was grown at 450 oC by water-plasma chemical vapor deposition using ultrathin iron on alumina supporting film. The growth rate of the SWNT forest is ~ 0.9 μm/min, and the diameters of nanotubes are mainly in a range of 3.0 ~ 3.5 nm. The low intensity ratio of D- to G-band (ID/IG ~ 0.098) in Raman spectra indicates that our SWNT forest grown at 450 oC is fairly pure and crystalline. This low temperature growth of SWNT forest may enable variable applications requiring the vertically-aligned nanotubes to obtain large surface area. KCI Citation Count: 7